Segregation of Eastern Filbert Blight Disease Response and Single Nucleotide Polymorphism Markers in Three European–American Interspecific Hybrid Hazelnut Populations - Justin J. Lombardoni; Josh A. Honig; Jennifer N. Vaiciunas; Ronald S. Revord; Thomas J. Molnar (Journal of the American Society for Horticultural Science, 2022)
The perennial stem canker disease eastern filbert blight (EFB), caused by Anisogramma anomala, is devastating to most trees of European hazelnut (Corylus avellana), as genetic resistance is rare in the species. The pathogen is harbored by the wild American hazelnut (Corylus americana) found throughout much of eastern North America. Wild American hazelnut is generally resistant or tolerant to EFB, and is fully cross compatible with C. avellana, the species grown commercially for its nuts, making it a valuable resource for disease resistance breeding. The objective of this study was to identify quantitative trait loci (QTLs) associated with EFB resistance and tolerance in these two species. Three unrelated EFB-resistant C. americana selections [Oregon State University (OSU) 533.069 from Pennsylvania, OSU 403.040 from Nebraska, and OSU 557.122 from Wisconsin] were crossed with C. avellana ‘Tonda di Giffoni’ (TdG), a cultivar from Italy known to be tolerant of EFB. Their progenies, each containing 124 trees, were exposed to A. anomala through field inoculations and natural spread over 7 years, then each tree was evaluated for cumulative disease response. Results showed that disease response of all three populations exhibited a roughly normal distribution, indicating that resistance/tolerance was under multigenic control. An average of 2869 total markers were used to construct each population’s linkage map following genotyping, which included an average of 121 published simple sequence repeat markers to anchor linkage groups (LGs) to those of previous studies. Linkage maps were constructed for each parent of each population and used to map QTLs associated with EFB response. The subsequent analysis resolved five EFB-related QTLs across the three populations, highlighting three genic regions. Unexpectedly, only one QTL was identified from one of the three resistant C. americana parents, located on LG11 of the map of OSU 403.040, whereas three QTLs were found in a similar region on LG10 across the three maps of TdG, and a fifth QTL was found on LG6 of one TdG map. The lack of strong QTLs identified from the three EFB-resistant C. americana parents suggests that their resistance may be highly quantitative and not resolved within the constraints of this study. In contrast, tolerance from TdG appears to be conferred by a limited number of genes with relatively strong effects. Based on prior mapping work in European and American hazelnut where R genes have been located on LG2, LG6, and LG7, the QTLs associated with resistance/tolerance on LG10 and LG11 represent novel resistance regions. These QTLs present new targets for marker aided breeding, especially when pyramiding EFB resistance genes is a goal.